Biodeversity of Noctural Insect at Natural Recreation Park Danau Dendam Tak Sudah Bengkulu Province - Apriyanto, Enggar; Nurjana, Nurjana; Saprinurdin, Saprinurdin (Agrikan Jurnal Agribisnis Perikanan, 2022)
Nocturnal insects are insects that are active in night time and responsive to light. These insects have a role in ecological processes in an ecosystem, including swamp ecosystem. The research was conducted at The Natural Recreation Park Danau Dendam Tak Sudah Bengkulu Province. The purpose of this study was to determine the abundance, diversity, and dominance of nocturnal insect species in The Natural Recreation Park Danau Dendam Tak Sudah. The method that be used was a black light trap of 20 watts, 220 volts, which emits low ultra violet light with a wavelength of 300 – 400 nm. The results showed that there were 16 species of insects (11 species in open swamps and 13 species in vegetated swamps), with the highest abundance of Hydrobius fuscipes (50.15% or 823 individuals), (12.49% or 205 individuals), and Aulacoscelis Sp. . (10.36% or 170 individuals). The swamp forest in the Natural Recreation Park Danau Dendam Tak Sudah has moderate diversity of nocturnal insects, with the value of H' value was about 1.69 in open swamps, 1.66 in vegetated swamps, and 1.75 in swamp forests. Nocturnal insects have low dominance, with the index value of dominance (D) was 0.27 - 0.29.